Anyoni - Movrin, Vita (Matrika, 2023)
All elementary particles can be classified into two categories: fermions and bosons. Anyons do not belong to either of these categories. Their defining characteristic is an arbitrary phase, referred to as ”any”, acquired by the wave function when two particles are exchanged. Consequently, the wave function is neither symmetric nor antisymmetric with respect to the interchange of both particles. Such a phenomenon is not possible in three-dimensional space. However, it can be observed when the motion of electrons is confined to two dimensions, as quantum statistics in this case becomes a reflection of the topology of worldlines. The most intriguing experimental phenomenon is the so-called quantum Hall effect, which has stimulated theoretical interest in anyonic quasi-particles, whose existence can explain this effect. In the article, we explore the key concepts crucial for understanding this phenomenon and conclude with a description of recent experimental confirmation of anyons.
Keywords: anyoni; anyons; fizika osnovnih delcev; kvantni Hallov pojav; physics of elementary particles; quantum Hall effect